Tax Avoidance Analysis through Capital Intensity, Inventory Intensity, and Leverage (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to present evidence on the effect of capital intensity, inventory intensity, and leverage disclosure on tax avoidance. This research utilizes secondary data from financial statements sourced from www.idx.co.id and the official websites of companies in the property and real estate sectors using quantitative research. The proxy used in measuring tax avoidance is using the effective tax rate (ETR) as the dependent variable and the independent variables used include capital intensity, inventory intensity, and leverage. Multiple linear regression analysis is the analysis technique used. The property and real estate sector listed on the IDX in the period 2021 to 2024 is the population in this study and the number of samples collected is 85 data obtained using the purposive sampling method. The findings of this research indicate that capital intensity, inventory intensity, and leverage significantly influence tax avoidance positively. These findings suggest that the higher the level of investment in fixed assets, inventory, and debt-to-equity ratio, the greater the tendency of a company to engage in tax avoidance.